Behavior of PtPb/MgAl2O4 catalysts with different Pb contents and trimetallic PtPbIn catalysts in n-butane dehydrogenation - Bocanegra, Sonia Alejandra (2013)
The behavior of PtPb/MgAl2O4 catalysts in butenes production through the n-butane dehydrogenation has shown that at low contents, the Pb acts as promoter, improving the conversion and selectivity, whereas at higher contents it has a poisoning effect on the catalytic activity. The PtPb(0.25 wt%)/MgAl2O4 catalyst showed the maximum yield to butenes. The characterization results of PtPb catalysts displayed that at low Pb contents there are both dilution and electronic effects of Pb on the Pt sites. On the other hand, at high Pb contents, there is a strong blocking effect of the Pb on the active sites of Pt. In order to study the effect of the In addition in different sequences to PtPb(0.25 wt%)/MgAl2O4 catalyst, two catalysts were prepared: PtPb(0.25%)In(0.28 wt%)/MgAl2O4 and PtIn(0.28%)Pb(0.25 wt%)/MgAl2O4. The first catalyst did not show significant advantages with respect to the catalytic behavior of the PtPb(0.25 wt%)/MgAl2O4, but the second trimetallic catalyst displayed an increase of both the conversion and the selectivity. The characterization results indicated similar effects of blocking and dilution of promoters on the active sites of Pt for both trimetallic catalysts, but the best catalyst, PtIn(0.28%)Pb(0.25 wt%)/MgAl2O4, showed the highest percentages of In◦ and Pb◦, thus indicating stronger interaction between Pt, Pb and In.